1999
DOI: 10.1021/ic981039w
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Aspects of Sulfur Recovery from Pd2I2(μ-S)(μ-dpm)2Using I2and Structures of Pd(II) Complexes with the Chelated Monosulfide of dpm

Abstract: The Pd(2)X(2)(&mgr;-S)(dpm)(2) complexes (2) (X = I, Br) react with halogens to yield PdX(2)(dpm) (3) and elemental sulfur. Kinetic and mechanistic studies on the X = I system in CHCl(3) reveal that the reaction proceeds via addition of I(2) to give Pd(2)I(4)(dpm)(2) (4c), which then undergoes unimolecular decomposition to generate PdI(2)(dpm) (3c); the liberated sulfur concatenates to form elemental S(8). The addition reaction is in the stopped-flow time regime and is first-order in both 2c and I(2), with Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…This phosphorus is coupled through the metal to the phosphorus nucleus of the arene-tethered ligand ( 2 J P-P = 35.7 Hz), as well as to the phosphine sulfide with J P-P = 19.7 Hz. This latter coupling is decreased with respect to the free ligand (49 Hz) [18], which is the usual observation [18][19][20][21][22] and is indicative of a spin coupling contribution of opposite sign through the metal and thus indicates the coordination of the sulfur to the metal. Likewise, the phosphine of the arene-tethered ligand shows a coupling to the directly coordinated phosphine of diphos(S), but an additional smaller 3 J coupling of 19.7 Hz to the phosphorus atom (the P V ) bound to the sulfur is observed.…”
Section: Resultsmentioning
confidence: 51%
“…This phosphorus is coupled through the metal to the phosphorus nucleus of the arene-tethered ligand ( 2 J P-P = 35.7 Hz), as well as to the phosphine sulfide with J P-P = 19.7 Hz. This latter coupling is decreased with respect to the free ligand (49 Hz) [18], which is the usual observation [18][19][20][21][22] and is indicative of a spin coupling contribution of opposite sign through the metal and thus indicates the coordination of the sulfur to the metal. Likewise, the phosphine of the arene-tethered ligand shows a coupling to the directly coordinated phosphine of diphos(S), but an additional smaller 3 J coupling of 19.7 Hz to the phosphorus atom (the P V ) bound to the sulfur is observed.…”
Section: Resultsmentioning
confidence: 51%
“…Some phosphine sulfides have been employed as monodentate or bidentate ligands for some metal ions [1][2][3][4][5][6], and we have applied multidentate phosphine sulfide ligands to the Pd(0) catalyzed CÀC coupling reaction to stabilize the zerovalent oxidation state of palladium [7]. However, so far, kinetic study on phosphine sulfide formation reactions of phosphine complexes has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The usual [7,9,17,21] lowering in the bis(phosphanyl) monosulfide ( 31 P, 31 P) coupling constants is observed in both the neutral and cationic complexes: compared with the 2/3 J(P,P) of the free ligands [for dppmS 2 J(P,P) ϭ 79 Hz, for dppeS 3 J(P,P) ϭ 49 Hz], a decrease of 50 Hz and 41 Hz was found for 1 and 2 and a decrease of 55 Hz and 42 Hz was found for 3 and 4, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%